2019
DOI: 10.2147/ijn.s217038
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Angiogenic Activity Of Bevacizumab-Bearing Dexamethasone-Loaded PLGA Nanoparticles For Potential Intravitreal Applications</p>

Abstract: PurposeAge-related macular degeneration is a multifactorial disease involving inflammation and choroidal neovascularization. Vascular endothelial growth factor (VEGF) has been regarded as a potential therapeutic target to treat choroidal neovascularization. Dexamethasone can interfere with the expression or action of VEGF while bevacizumab targets and combines with VEGF. We propose electrostatically-conjugated bevacizumab-bearing dexamethasone-loaded poly (D,L-lactide-co-glycolide)/polyethylenimine nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…The aBev/cRGD-DPPNs were prepared by the adsorption method based on the method reported before [ 36 ]. A certain mass of bevacizumab and the cRGD-DPPNs were co-dispersed in PBS (pH 8.0) for 2 h at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aBev/cRGD-DPPNs were prepared by the adsorption method based on the method reported before [ 36 ]. A certain mass of bevacizumab and the cRGD-DPPNs were co-dispersed in PBS (pH 8.0) for 2 h at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The tube formation assay of capillary-like structures inhibition was performed as described previously [ 36 , 38 ]. The 300 μL matrix gel (8.6 mg/mL) was added to the 24-well plates on ice and kept at 37 °C for 30 min to polymerize into the membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu et al [ 35 ] proved that the use of these micelles improved retinal dysfunctions, inhibited retinal leukostasis, diminished retinal vascular leakage and regulated the over expression of vascular endothelial growth factor (VEGF) at eight weeks after the application. Lui et al [ 36 ] described a similar PLGA/PVA based on micelles to treat choroidal neovascularization. In this case, the polymer system also included polyethyleneimine (PEI) to incorporate positive charges in the NP, while the medication was a combination of dexamethasone and bevacizumab, which can interact with the positive charges of PEI.…”
Section: Polymeric Nanocarriers For Ocular Drug Deliverymentioning
confidence: 99%
“…Ye et al prepared PLGA nanoparticles loaded with bevacizumab that were administered intravitreally into rabbit eyes; a substantial increase in the following pharmacokinetic parameters was achieved: intravitreal half-lives, mean concentration, and bioavailability compared with those of the free drug [ 99 ]. After developing dexamethasone-loaded PLGA/PEI nanoparticles with conjugated bevacizumab for a CNV model, Liu et al proposed a strong anti-angiogenic effect as demonstrated via in vitro and in vivo studies [ 100 ].Qiu et al designed fenofibrate-loaded PLGA-nanoparticles that were injected intravitreally into the eyes of rats with diabetic retinopathy and a neovascularization model. Accordingly, reduction of retinal vascular leakage, suppression of VEGF and CNV formation, and inhibition of retinal leukocytosis were observed [ 101 ].…”
Section: Efforts To Enhance the Intraocular Pharmacokinetics And Pmentioning
confidence: 99%